2022
DOI: 10.1093/cercor/bhac049
|View full text |Cite
|
Sign up to set email alerts
|

Continuous theta burst stimulation over left and right supramarginal gyri demonstrates their involvement in auditory feedback control of vocal production

Abstract: The supramarginal gyrus (SMG) has been implicated in auditory-motor integration for vocal production. However, whether the SMG is bilaterally or unilaterally involved in auditory feedback control of vocal production in a causal manner remains unclear. The present event-related potential (ERP) study investigated the causal roles of the left and right SMG to auditory-vocal integration using neuronavigated continuous theta burst stimulation (c-TBS). Twenty-four young adults produced sustained vowel phonations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…In contrast, prolonged peak times of vocal responses were found when inhibitory cTBS was applied over the left DLPFC (Liu et al, 2020). Other NIBS studies targeting other brain regions have shown that a-tDCS over the right cerebellum prolonged the peak times of vocal responses to pitch perturbations (Peng et al, 2021), while cTBS over the right cerebellum (Lin et al, 2022) or the left or right SMG (Li et al, 2023) shortened them. Prolonged vocal responses to pitch perturbations have been observed in patients with PD (Kiran and Larson, 2001) or aphasia (Johnson et al, 2020), reflecting their impaired sensorimotor integration in speech processing.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, prolonged peak times of vocal responses were found when inhibitory cTBS was applied over the left DLPFC (Liu et al, 2020). Other NIBS studies targeting other brain regions have shown that a-tDCS over the right cerebellum prolonged the peak times of vocal responses to pitch perturbations (Peng et al, 2021), while cTBS over the right cerebellum (Lin et al, 2022) or the left or right SMG (Li et al, 2023) shortened them. Prolonged vocal responses to pitch perturbations have been observed in patients with PD (Kiran and Larson, 2001) or aphasia (Johnson et al, 2020), reflecting their impaired sensorimotor integration in speech processing.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, we found that SMG was involved in ARHL compared with healthy controls. On the one hand, the SMG can be activated by pure tones and is causally implicated in auditory-motor integration ( 24 ). On the other hand, the SMG becomes a convergence zone of various networks associated with attention and verbal working memory ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, cTBS over right, but not left pSTG resulted in reduced compensations for pitch perturbations accompanied by smaller N1 and larger P2 responses in Mandarin speakers. In contrast, both the left and right supramarginal gyrus (SMG) has been found to causally contribute to pitch compensation in Mandarin speakers ( Li et al, 2022 ).…”
Section: Neurobiology Findingsmentioning
confidence: 99%
“…By combining AAF paradigm with brain stimulation and neuroimaging techniques, a series of studies have been conducted by Liu’s group to investigate the neural basis of pitch control in tonal language speakers (e.g., Liu et al, 2020 , 2023 ; Li et al, 2022 ). They have demonstrated the causal role of left dorsolateral prefrontal cortex (DLPFC) in pitch compensation by showing that inhibitory continuous theta burst stimulation (cTBS) over DLPFC elicited larger compensatory responses and smaller event-related potential (ERP) P2 responses in Mandarin speakers experiencing pitch perturbation (+200 or +500 cents), compared to sham stimulation ( Liu et al, 2020 ).…”
Section: Neurobiology Findingsmentioning
confidence: 99%